Hear me Ohio - Hirt, Jen, 1975- (Ohio history and culture., 2020)
"Hear Me Ohio is a collection of essays about leaving Ohio while always looking back at it from places as far and different as Idaho, to the familiar forest of an arboretum in Kentucky, to the Pennsylvania riverbanks of the Susquehanna River. Hirt writes about loss and discovery, but also horseradish and hold-ups, unicorns and spiders, chestnuts and dobsonflies, dogs and kayaks. Readers will find nature writing, meditations, literary journalism, and memoir-a range of approaches for covering a range of miles and years since a childhood spent growing up in Hirt's Greenhouse in Strongsville, Ohio, which was the subject of her first book"--